Islamic architectural heritage in Malaysia - Mohd Nawawi, Norwina (2014)
Islamic architecture and Islamic architectural heritage speak volume of the essence and values of the people of the Islamic faith as a physical manifestation within the environmental context they were and currently positioned. This introductory paper to Islamic Architectural Heritage Research Unit (ISArcH) is to provide the vision and mission of the unit incongruent to the International Islamic University Malaysia’s inspiration to be a champion of truth on architecture and architectural heritage based on Al-Quran and Sunnah, for the benefit of Mankind. The presentation dwells briefly on the semantics and definition to provide the framework of the discussion on Islamic architectural heritage in general and the context of Malaysia. The scope of the deliberation provides the tangible and intangible area of the built environment to which examples of research and heritage studies learned from the past for the benefit of the future society are presented. The presentation concluded with the proposed area of research, projects and activities as well as networking that the unit can pivot as a platform in harvesting, acknowledging and practice of the man-made built environment as Allah has envisaged for Mankind as submission to Him.